PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS KONSTRUKTIVISME PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMPN 23 PADANG - Syahdi, Septri - (STKIP PGRI Sumbar, 2014)
The research is based on the consideration of the importance of teaching materials that used by student but give enough chance for student to build their own understanding. Besides that, students are also not well guided enough to find the concept and connect it with daily life. Due to the reasons, teaching materials called student work sheet or workbook based construction of get up the flat side are developed class eight in SMPN 23 Padang. The aim of this research is to find out the validity and practicality of the workbook that based on construction of get up the flat side. The type of this research is development of 4-D model. The 4-D model consists of 4 development stages : define, design, develop and desseminate. However, the researcher only used 3 stages in this research : get up the flat side. The develop stages is done by developing the workbook and testing the validity and practicality. The analysist of workbook done descriptive way and the result of validity is 3,42 which the highest point of validity. The result of the practicality testing is very high which 86,90 %. It means the workbook based construction of get up the flat side class eight in SMPN 23 Padang is valid and practical.